Tree and Landscape as an image of place. - Biedermann, Anton; Art Focus Contemporary Israeli Art, Jerusalem 1994 (Hadera : Studio Oman, 1994)
Shalev, Neomi ; Regev, Reviva ; Recanati, Mira ; Averbuch, Shlomit ; Enbar, Nachum ; Hatzofe, Emanuel ; Zakai, Shai ; Sharabi, Zivit ; Cohen Levy, Maya ; Reuven, Roni ; Camal, Natur ; REgev, Batia ; Kedar, Dorith ; Hamdan, Faris ; Helvitz, Ruth ; Shevi, Orly ; Biedermann, Anton ; Grifith, Joshua ; Abu-Rukun, Yousuf ; Mark, Yossi, Ezra, Avi ; Rubin, Yadid
Tree and Landscape as an image of place, Studio Oman, Hadera, October 1994. Art Focus Contemporary Israeli Art, Jerusalem 1994
boek